KARAMBI: LEARNING MEDIA EXCRETION SYSTEM FOR HIGH SCHOOL CLASS XI - Nurfadila, Nurfadila; Misykat Malik Ibrahim; Ali, Ahmad (Universitas Islam Negeri Alauddin Makassar, 2022)
Karambi learning media is a board game played by several people and there is an element of teamwork. Karambi learning media has several advantages such as training focus, fostering curiosity, increasing interest and motivation and increasing student activity in learning. This research is included in Research and Development to develop a valid, practical and effective Karambi learning media. This study adapts the development model of Tjeerd Plomp (1997) which consists of several stages, namely preliminary research (Preliminary Investigation), design phase (Design), realization/construction phase (Realization/construction), test phase, evaluation and revision (Test, Evaluation and Revision), as well as the implementation phase (Implementation) . However, at the implementation stage it was only carried out on a limited scale, namely in class XI MIPA SMAN 5 Soppeng. The target of this research is the students of class XI MIPA 1 SMAN 5 Soppeng, totaling 28 students. The research instrument used is a questionnaire and items. Questionnaires are used to measure practicality, while items are used to measure the effectiveness of Karambi's media. The results of the study indicate that the Karambi learning media developed on the excretory system material has a validity value of 3.78 with a very valid category, the level of practicality based on the results of the questionnaire shows a practical category with a total value of 3.48. While the level of effectiveness of the media based on the test of student learning outcomes is categorized as effective because it reaches 100% completeness value. The implications of this research are 1) Karambi learning media on the excretory system material can be used as a media to support learning. 2) Karambi learning media is feasible to be applied as a learning medium to increase student activity. 3) Karambi learning media can be implemented in other schools with various biological materials.